Partisipasi Masyarakat Dalam Penyusunan Peraturan Desa Di Indonesia - Heny Noniarti; Eliza Yuliana; Muhammad Harismansyah Putra Arifin; Alimni Alimni; Ismail Ismail (Qiyas : Jurnal Hukum Islam dan Peradilan, 2023)
Abstract: There is an obligation to involve the community in drafting village regulations. Therefore, this conceptual article is intended to find out how the process of community formation and participation in the preparation of village regulations is carried out. The approach used is the statute approach by collecting primary and secondary legal materials which are then analyzed descriptively. The results, first, are the stages of forming village regulations starting from planning, drafting, discussing, stipulating, promulgating, to dissemination. Second, community participation in the preparation of village regulations is a form of democratic political relations in village governance. In addition, the intended participation can be used as a means to discuss and agree on strategic matters.Keywords: Society Participation; Village Regulation.